2016
DOI: 10.1038/srep33484
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in Monochamus alternatus digested with azadirachtin

Abstract: The pine sawyer beetle Monochamus alternatus Hope, a major forest insect pest, is the primary vector of the destructive forest pest pine wood nematode, Bursaphelenchus xylophilus. Azadirachtin, an active compound of neem, is biologically interesting because it represents a group of important, successful botanical pesticides. We provide insight into the molecular effects of azadirachtin on M. alternatus at the transcriptional level to provide clues about possible molecular-level targets and to establish a link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The most significantly enriched GO terms in biological processes, cellular components and molecular functions for E11_VS_E16, E16_VS_P1 and E11_VS_P1 comparison groups (Figure 8 ). GO is gene functional classification system which offers a dynamic-updated vocabulary to widely describe properties of genes and their products in an organism [ 17 , 18 ]. We performed GO analysis by using differential expressed gene against the GO ( http://www.geneontology.org/ ).…”
Section: Resultsmentioning
confidence: 99%
“…The most significantly enriched GO terms in biological processes, cellular components and molecular functions for E11_VS_E16, E16_VS_P1 and E11_VS_P1 comparison groups (Figure 8 ). GO is gene functional classification system which offers a dynamic-updated vocabulary to widely describe properties of genes and their products in an organism [ 17 , 18 ]. We performed GO analysis by using differential expressed gene against the GO ( http://www.geneontology.org/ ).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have investigated the differential expression of immunity-related genes in M. alternatus in relation to insecticides like imidachloprid and azadirachtin (Lin et al 2015(Lin et al , 2016. However, to the best of our knowledge, the present study is the first to demonstrate differential expression of immunity-related genes in M. alternatus parasitized by its natural enemy at the transcription level.…”
Section: Resultsmentioning
confidence: 48%
“…Calcium is a common second messenger that regulates many processes in cells 29 . In our experiments, insect cells were used because this allows us to measure azadirachtin effects on the calcium channel function in a manner which preserves intracellular modulations of ion channel functions 30 , 31 . We found that azadirachtin could induce an increase of intracellular Ca 2+ release in Sf9 cell.…”
Section: Discussionmentioning
confidence: 99%